Dynamic Alterations in the Respiratory Tract Microbiota of Patients with COVID‐19 and its Association with Microbiota in the Gut (Adv. Sci. 27/2022). Issue 27 (23rd September 2022) - Shen, Yifei; Yu, Fei; Zhang, Dan; Zou, Qianda; Xie, Mengxiao; Chen, Xiao; Yuan, Lingjun; Lou, Bin; Xie, Guoliang; Wang, Ruonan; Yang, Xianzhi; Chen, Weizhen; et al.
Abstract : COVID‐19 The study presented in article number 2200956 by Shufa Zheng, Yu Chen, and co‐workers, shows that dynamic changes occur in the respiratory tract and gut microbial communities of COVID‐19 patients with different disease severity and that significant changes in the composition of the respiratory tract and gut microbiomes can be found between intensive care unit (ICU) and non‐ICU patients.